Achieving Competitive Advantage of SMEs in Malang City through Resource Based View, Entrepreneurship Orientation, and Innovation - Stevanny Elsa Dyah Ayu Rigan; Cesya Rizkika Parahiyanti (Jurnal Manajemen dan Kewirausahaan, 2022)
This explanatory study aimed to examine the mediating role of innovation in influencing resource-based view strategy and entrepreneurial orientation on competitive advantage. The samples taken in the study were 100 handicraft Small and Medium Enterprises (SMEs) in Malang, Indonesia. The data was collected using a quantitative approach by distributing a survey. Validity and reliability tests have been passed before testing the actual data analysis with SEM-PLS. The results indicate that innovation significantly mediates resource-based view strategy and entrepreneurial orientation on competitive advantage. If SMEs strive to achieve a highly competitive advantage through resource-based view strategies and entrepreneurial orientation, the ability to innovate has an essential role in this relationship. Hence, SMEs need to have good resources and adequate skills to enhance attitudes such as continuously developing innovative products, being brave in taking existing risks, and always making innovations. These strategy options can help the success in achieving a competitive advantage.